A calcified cervical intervertebral disc in child and a thoracic disc calcification in an adult with posterior herniation-radiographic, computed tomography and magnetic resonance imaging findings - Jevtič, Vladimir (Radiology and oncology (Ljubljana), 2004)
Background. Nucleus pulposus calcification in children is a relatively rare but well known clinical syndrome, usually localized at the level of the cervical spine. The exact aetiology still remains uncertain. Calcifications ofthe intervertebral discs in adults differ from the childhood variety. They are mainly degenerative in nature and occur at the level of midthoracic and upper lumbar spine. Potentially serious complications, posterior herniation ofcalcified disc may occur in both entities. Case reports. We report two casesof the calcification of the nucleus pulposus in a seven-year-old boy at the level of C7-T1 and a case of calcified intervertebral disc T11-T12 in a forty five-year-old woman, with massive posterior herniation. Remission of symptoms was achieved with a conservative therapy alone. Clinical, radiographic, computed tomographic and magnetic resonance imaging (MRI) findings were analyzed in an attempt to investigate similarities and differences between both disease entities. Conclusion. Massive posterior herniation of calcified nucleus pulposus in a child was treated conservativelywith a favourable outeome. A disappearance of symptoms followed guick resolution of herniated calcified masses. In adult variety extruded thoracic disc calcification was of a permanent type with no tendency towards spontaneous resolution and remission of symptoms after the conservative therapy. MRI seems to be able to depict disc calcification before a conventional radiography. The widening of affected discs in a paediatric patient was also better demonstrated by MRI It would seem to support the theory of an increased intradiscal pressure as the precursor of annulus fibrosus ruptures and consecutive calcified disc herniations.
Keywords: Calcinosis; diagnostika; hrbtenica; Hrbtenica, bolezni; Intervertebral Disk; Intervertebral Disk Displacement; kalcifikacija; Kalcinoza; Magnetic Resonance Imaging; Magnetna resonanca slikovna; Medvretenčna ploščica; Medvretenčna ploščica, hernija; Radiography; radiologija; Spinal Diseases; therapy; Tomografija radiografska, računalniška; Tomography, X-Ray Computed; zdravljenje